In vitro and in vivo effects of rifabutin alone or combined with atovaquone against Toxoplasma gondii. - Romand, S (1996)
The efficacy of rifabutin (RIFA) alone or in combination with atovaquone (ATO) was examined in vitro and in a murine model of acute toxoplasmosis. In vitro studies were performed with MRC5 fibroblast tissue cultures, with quantification of Toxoplasma growth by enzyme-linked immunosorbent assay. For in vivo studies, mice were acutely infected with 10(4) tachyzoites of the virulent RH strain and were then treated perorally for 10 days from day 1 or day 4 postinfection. The efficacy of each drug regimen was assessed by determination of survival rates and sequential titration of parasites in blood, brain, and lungs by a tissue culture method. In vitro, RIFA was inhibitory for Toxoplasma growth at concentrations between 0.5 and 20 micrograms/ml; the 50% inhibitory concentration was estimated to be 1.68 micrograms/ml. When RIFA and ATO were combined, synergistic effects were noted for RIFA at 20 micrograms/ml combined with ATO at 0.01 or 0.02 microgram/ml and RIFA at 1, 2, or 5 micrograms/ml combined with ATO at 0.02 microgram/ml. In vivo, administration of RIFA at 200 mg/kg of body weight per day from day 1 to day 10 resulted in a 100% protection during treatment, with clearance of parasites from the blood, brain, and lungs. After the cessation of therapy, relapses occurred in the brain and lungs; the mortality was 46% at the end of the experiment (day 30). Among the mice treated with RIFA at 200 mg/kg/day from day 4 to day 14, no death was recorded during the treatment period and a marked reduction in parasite burdens was observed in blood and tissues; however, relapses occurred and 10% of mice survived until day 30. Administration of RIFA at 200 mg/kg/day in combination with ATO at 100 mg/kg/day resulted in a marked prolongation of survival compared with that for mice that received ATO or RIFA alone. However, in mice receiving the combination, parasite burdens in blood and organs were similar to those in mice treated with RIFA alone. These results confirmed the activity of RIFA in the treatment of acute toxoplasmosis and the potential of the combination of RIFA-ATO since the two drugs act synergistically against Toxoplasma gondii.